(untitled) (International Journal of Physiotherapy, 2016)
Background: Chronic low back pain remains a major health problem. Unfortunately, the majority of treatments for this condition produce small effects because not all patients respond to each treatment. It appears that only 25–50% of patients respond to exercise. At present, however, there are no guidelines regarding the best treatment to help clinicians. As a result, time and money are wasted on treatment which ultimately fail to help the patient. A backache is described as annoying and gripping pain. It can be caused by poor posture, lack of manual handling skills, change in the center of gravity due to expanding abdomen, lack of exercise, or the weight of the baby and the stretching ligaments. Pelvic floor muscle weakness is one of the major cause of chronic backache. Weakness in the pelvic floor muscles is common in females which can lead to debilitating urinary symptoms, affect sexual function and cause chronic backache. Methods: In 3 months, 31 female subjects with mean age of 28 who had taken treatment for their chronic backache, were improvised with pelvic floor strength at our setup, with dramatically good results. 31 subjects with non-responsive chronic back pain who had taken conventional physiotherapy were included in the study. Both married and unmarried were included. Any sign of radiculopathy or inflammation were excluded. After assessing pain using Visual Analogue Scale, the Dr Glazer’s program and Kegel’s contractions were taught. Results: There was significant improvement by 50% on reassessment after 7 days. Then exercises for transverse abdominals were included to get a better response. On completion of the treatment sessions, reduction in pain was 92% on VAS and functional abilities increased by 89%. There was a significant improvement in the quality of life and in pelvic-floor muscle strength. Conclusion: Non-responsive chronic back pain in females when treated with pelvic floor muscle strengthening program showed 40% improvement. This can be implemented in routine practice for the benefit of the patients.